2018
DOI: 10.1002/adma.201800726
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented Stimuli‐Controlled Single‐Crystal Reversible Phase Transition of a Metal–Organic Framework and Its Application to a Novel Method of Guest Encapsulation

Abstract: The flexibility and unexpected dynamic behavior of a third-generation metal-organic framework are described for the first time. The synthetic strategy is based on the flexibility and spherical shape of dipyridyl-based carborane linkers that act as pillars between rigid Co/BTB (BTB: 1,3,5-benzenetricarboxylate) layers, providing a 3D porous structure (1). A phase transition of the solid can be induced to generate a new, nonporous 2D structure (2) without any loss of the carborane linkers. The structural transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…This phenomenon indicated that the RPT behavior of YNU‐1 opened up a new strategy to encapsulate guests that exceeded the pore size of MOFs. A similar phenomenon was also reported by Planas et al …”
Section: Applicationssupporting
confidence: 90%
See 3 more Smart Citations
“…This phenomenon indicated that the RPT behavior of YNU‐1 opened up a new strategy to encapsulate guests that exceeded the pore size of MOFs. A similar phenomenon was also reported by Planas et al …”
Section: Applicationssupporting
confidence: 90%
“…B) Optimized conditions for the bulk reversible 1 to 2 transformation and C 60 encapsulation (Reproduced with permission from ref. ).…”
Section: Different External Stimulimentioning
confidence: 97%
See 2 more Smart Citations
“…This MOF behaves like a spin-crossover magnet, where strong mutual switching between photo-emitted Fe II and neighboring Nb IV atoms works through C-N bridges. [97] Light can also stimulate the transition between two structural states in MOFs with special photochromic molecules as ligands or guests. [96] The 3D niccolite MOF mentioned earlier, [(CH 3 CH 2 ) 2 NH 2 ] [Fe III Fe II (HCOO) 6 ], also appeared to demonstrate magnetic hysteresis regulated by a thermal and magnetic state at low temperatures, [80] a phenomenon which is the response of the magnetization of Fe II and Fe III sublattices to external stimuli.…”
Section: Bistabilitymentioning
confidence: 99%